Systematic Literature Review : Analisis Penerapan Network Models dalam Kehidupan Sehari-Hari - Cici Wulandari; Farizi Aqfi; Saprina Maulida; Sazatul Asmal; Siti Zia Hadatul Hasanah; Sri Rahayu Ningsih; Siti Salamah Br Ginting (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study examines the application of network models in daily life using a systematic literature review (SLR) method. Network models are mathematical approaches that aid in solving various optimization problems such as shortest routes, minimum spanning trees, and maximum flows. Findings reveal that the Floyd-Warshall and Dijkstra algorithms are applied for route navigation, Prim's algorithm for distribution efficiency, and the Edmonds-Karp algorithm for optimizing resource flows like water. This research highlights the significance of network models in enhancing operational efficiency, sustainability, and accessibility across various domains such as transportation, logistics, and resource management. With the integration of modern technology, network models hold significant potential for developing innovative solutions in everyday life.